Environmentally benign silver bio-nanomaterials as potent antioxidant, antibacterial, and antidiabetic agents: Green synthesis using Salacia oblonga root extract - Dugganaboyana, Guru Kumar; Kumar Mukunda, Chethan; Jain, Anisha; Kantharaju, Raghavendra Mandya; Nithya, Rani R.; Ninganna, Divya; Ahalliya, Rathi Muthaiyan; Shati, Ali A.; Alfaifi, Mohammad Y.; Elbehairi, Serag Eldin I.; Silina, Ekaterina; Stupin, Victor; et al. (Frontiers in Chemistry, 2023)
Introduction: The use of plant extracts in the green synthesis of metallic nanoparticles is one of the simplest, most practical, economical, and ecologically friendly methods for avoiding the use of toxic chemicals. Method: Silver nanoparticles (AgNPs) were synthesized, employing a high-efficiency, non- toxic, cost-effective, green, and simple technique that included the use of Salacia oblonga root extract (SOR) as a capping agent compared to synthetic nanoparticles. The use of S. oblonga can be seen in traditional medicines for treating diabetes, obesity, rheumatism, gonorrhea, asthma, and hyperglycemia. The objectives of the current study were to green synthesize S. oblonga root extract silver nanoparticles (SOR-AgNPs), characterize them, and study their antioxidant, antibacterial, and antidiabetic activities. Result: The shape of SOR-AgNPs was spherical, at less than 99.8 nm in size, and exhibited a crystalline peak at XRD. The green synthesized SOR-AgNPs showed significant antioxidant properties like DPPH (80.64 μg/mL), reducing power capacity (81.09 ± SEM μg/mL), nitric oxide (96.58 μg/mL), and hydroxyl (58.38 μg/mL) radical scavenging activities. The MIC of SOR-AgNPs was lower in gram-positive bacteria. The SOR-AgNPs have displayed efficient inhibitory activity against α-amylase, with an EC50 of 58.38 μg/mL. Analysis of capping protein around the SOR-AgNPs showed a molecular weight of 30 kDa. Discussion: These SOR-AgNPs could be used as antibacterial and antidiabetic drugs in the future as it is cheap, non-toxic, and environmentally friendly. Bio-fabricated AgNPs had a significant impact on bacterial strains and could be used as a starting point for future antibacterial drug development.